Exercício físico e HIV: revisão histórica, ensaio clínico aleatório em humanos e estudos experimentais em camundongos - Guariglia, Débora Alves (2016)
Exercise has been a widely used strategy to improve the health of people living with HIV/AIDS, especially for its role in combating the side effects of antiretroviral therapy. Thus, the aim of the current work is to investigate on the topic exercise in people living with HIV/AIDS. To reach such purpose four works with the following objectives were developed: a) a literature review with the objective to carry out a historical review on the prescription of aerobic, resistance and combined exercise in adults living with HIV; b) a randomized clinical trial in order to check the impact of 16 weeks of combined training on body composition and plasma biochemical variables of people living with HIV/AIDS users of antiretroviral therapy (ART); c) and two experimental studies aiming to test the induction of lipodystrophy syndrome characteristics in mice undergoing a derived drug therapy of HAART; and study the effect of exercise in mice chronically treated with drugs on TARV with similar physiological changes observed in patients under the same systematic therapy. After the development of these investigations were found 68 exercise articles in people living with HIV/AIDS. Currently, the most adopted strategies for the physical training of this population are the combined and resistance exercise. For the human study, it was found that 16 weeks of combined training were able to significantly reduce body fat being these responses more pronounced when analyzed the android region in patients with lipodystrophy. The experimental studies conducted in mice initially observed possible partial induction of lipodystrophy treated by the antiretroviral therapy. However, in the second study, it was observed that 4 weeks of training in animals treated with HAART are not sufficient to modify the established parameters of the lipodystrophy induction. Thus, it is possible to conclude that in the last 10 years resistance and combined training has been the most popular, and the effect of combined training in people living with HIV/AIDS is the reduction of body fat in different regions. In addition, antiretroviral therapy is capable of promoting lipodystrophy-like effects in mice and 4 weeks of aerobic exercise is not effective to reverse these effects.